Correlation analysis of biotechnology theme project-based learning with students creative thinking skills at the junior high school - Aminatul Husna; Sudarti Sudarti; Rif’ati Dina Handayani (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2023)
Learning is a core element in education, especially in achieving the goals of educational institutions. Through science learning, students can improve their self-esteem and understand their natural surroundings. Science learning involves scientific methods to develop students' thinking patterns. Project-based learning aims to develop conceptual understanding through investigating significant problems and producing products. The learning model must also be tested for its influence on students' creative thinking abilities, including biotechnology material. This study aims to determine the significant correlation between project-based learning and students' creative thinking skills. This study uses a quantitative approach. The statistical test uses the Pearson product-moment correlation analysis technique. The data showed a positive relationship between biotechnology-themed project-based learning and students' creative thinking skills. Project-based learning can help students improve creative thinking skills and be more contextual or meaningful so students can easily remember them.Abstrak Belajar adalah unsur inti dalam pendidikan, khususnya dalam mencapai tujuan lembaga pendidikan. Melalui pembelajaran IPA, peserta didik dapat meningkatkan kualitas diri dan memahami alam sekitar. Pembelajaran IPA melibatkan metode ilmiah untuk mengembangkan pola pikir peserta didik. Pembelajaran berbasis proyek bertujuan untuk mengembangkan pemahaman konseptual melalui penyelidikan masalah yang signifikan dan menghasilkan produk. Model pembelajaran juga perlu diuji pengaruhnya terhadap kemampuan berpikir kreatif peserta didik, salah satunya pada materi bioteknologi. Penelitian ini bertujuan untuk mengetahui hubungan yang signifikan antara pembelajaran berbasis proyek dengan keterampilan berpikir kreatif peserta didik. Penelitian ini menggunakan pendekatan kuantitatif. Pengujian statistik menggunakan teknik analisis korelasi product moment Pearson. Berdasarkan hasil data tersebut, diperoleh hubungan yang positif antara pembelajaran berbasis proyek bertema bioteknologi dengan keterampilan berpikir kreatif peserta didik. Pembelajaran berbasis proyek dapat membantu peserta didik untuk meningkatkan keterampilan berpikir kreatif dan lebih kontekstual atau lebih bermakna sehingga dapat dengan mudah diingat oleh peserta didik.